Thermally driven oxygen functionalization for durable Pt electrocatalysts in the oxygen reduction reaction - Kim, Min Woo; Lee, Jong Min; Jung, Chi-Young; Cha, Jung-Eun; Myung, Kwang Shik; Lee, Nam Jin; Kim, Nam Dong; Jung, Jae Young (Royal Society of Chemistry, 2025)
Enhancing the durability of platinum catalysts in proton exchange membrane fuel cells (PEMFCs) remains a key challenge for long-haul truck applications. In this study, we employed a commercialized high-surface-area carbon support and performed thermal annealing under oxidizing/reducing conditions to precisely control the oxygen functional groups on its surface. Subsequently, platinum nanoparticles (Pt NPs) were uniformly dispersed on the carbon support via a polyol method. We systematically investigated the Pt NPs/carbon interface effect using advanced spectroscopic techniques combined with electrochemical surface analyses, while isolating the effects of Pt location and pore structure. Consequently, we significantly improved the durability of the platinum catalyst, with mass activity retention increasing from 40.9% to 78.6% of initial performance (0.393-0.403 A mgPt-1), and the electrochemical surface area (ECSA) rising from 57.9% to 84.2% of initial ECSA values (95-97 m2 gPt-1). These improvements were achieved while maintaining highly precise initial parameters. Through extensive material characterization, we demonstrated that the improved durability of the platinum catalyst is attributed to the increased binding energy between the oxygen functional groups and Pt nanoparticles (NPs), as well as the suppression of Pt ionization. This study highlights the crucial role of carbon supports in fuel cells and provides guidelines for optimal design, paving the way for platinum catalysts intended for long-range fuel cell applications in areas such as ecofriendly hydrogen vehicles and distributed power generation.